The Effect of the Smoke-Free Workplace Policy in the Exposure to Secondhand Smoke in Restaurants, Pubs, and Discos in San Juan, Puerto Rico - Marín, Heriberto A.; Díaz-Toro, Elba (Puerto Rico Health Sciences Journal, 2010)
Background: Tobacco use and the involuntary exposition to secondhand smoke (SHS) is one of the leading causes of all cancers in the world. The objective of this study was to assess the effect of the smoke-free workplace policy implemented in March of 2007 in Puerto Rico on the exposition to secondhand smoke in restaurants, pubs, and discos of the metropolitan area of San Juan, Puerto Rico. Methods: The study used a pre-post comparison design on a random sample of 55 establishments (32 restaurants and 23 pubs and discos) in the metropolitan area of San Juan, Puerto Rico. Measurements of indoor concentrations of fine particulate matter (PM) (2.5 mm diameter, PM2.5) were taken before and after the introduction of the law banning smoking using a SidePak AM510 Personal Aerosol Monitor (TSI Company). Also, data on the number of smokers, number of customers, and establishment area was collected. Paired t-tests and linear regression analyses were used to test any statistically significant effect of the law. Results: After the smoking ban was implemented, restaurants experienced an 83.6% (p=0.013) reduction in the mean of PM 2.5 levels, from 0.169 to 0.028 mg/ m3, and pubs and discos experienced a 95.6% (p=0.004) reduction, from 0.626 to .028 mg/m3. Conclusion: The implementation of the smoke-free workplace policy considerably reduced the exposition to SHS of workers and customers in the restaurants, pubs, and discos of the metropolitan area of San Juan, Puerto Rico.